Una especie nueva de Euphyllia (Scleractinia: Caryophylliidae) en las calizas de Barra Honda (Paleógeno), Costa Rica - Aguilar, Teresita (2001)
A new species of scleractinian coral is described: Euphyllia donatoi. This is the first report of this genus from Central America. The outcrop is located on the north-west of Costa Rica. It consists of large colonies (1.2 m high by 0.5 m in diameter), from a patch reef which had a dendroid habit. They are part of a very distintive facies in a micritic limestones of the Barra Honda Formation (Paleogene). The finding is important because these are the only macrofossils found in Barra Honda Formation. The growth took place under unestable ecological conditions resulting in a low diversity autocthonous community. It probably developed in very shallow water with a high sedimentation rate.